Rozwój języka wykonawczego flecistów w muzyce jazzowej od roku 1913 do współczesności = The development of flutists performance language in jazz music from 1913 to the present day - Wiśniowski, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the development of the performance language of jazz flutists from 1913 to the present day. It contains the sources of inspiration as well as the meaning of mutual influences. It reveals the role of classical and avant-garde music in shaping the style of some jazz flutists. It appeals to the biographical facts, indicates the motives for which the described jazzmen took up the flute.
Keywords: flute; jazz; improvisations; articulation; jazz history; performance